Comparative studies of a new commercial kit for the estimation of vitamin B12 in serum. Issue 9 (September 1981) - Waters, H M; Thornton, J A; Stevens, R F; Gowenlock, A H; Maciver, J E; Delamore, I W
Abstract : A commercial kit method (Technia Diagnostics) for the estimation of serum vitamin B12 claiming certain practical advantages was examined. Analytical and clinical performance were compared with a non-commercial radioisotope B12 method, previously compared to other commercial radioisotope B12 methods. The kit's analytical performance in our hands was satisfactory, although the within-batch precision and recovery of added cyanocobalamin were disappointing. Clinical performance was comparable with the non-commercial B12 method. Establishment of suitable reference ranges as a prerequisite to diagnostic use is apparent.